Economic alternatives for growth, employment, and poverty reduction progressive policy recommendations for developing countries - McKinley, Terry; ProQuest (Firm) (New York : Palgrave Macmillan, 2009)
"This book is a collection of working papers, policy briefs and training modules, published by the International Poverty Centre in Brazil, which provides a comprehensives set of recommendations for alternative economic policies that can generate growth, employment and poverty reduction in developing countries"--Provided by publisher.
pt. I. Alternative macroeconomic policies. The macroeconomic implications of MDG-based strategies in sub-Saharan Africa / John Weeks and Terry McKinley ; Pro-growth alternatives for Monetary and financial policies in sub-Saharan Africa / Robert Pollin, Gerald Epstein and James Heintz ; Addressing global imbalances : a development-oriented policy agenda / Alex Izurieta and Terry McKinley -- pt. II. Economic consequences of scaling up ODA. The macroeconomic debate on scaling up HIV/AIDS financing / Terry McKinley and Degol Hailu ; Why is 'the Dutch Disease' always a disease? The macroeconomic consequences of scaling up ODA / Terry McKinley ; The impact of foreign aid on government spending, revenue and domestic borrowing in Ethiopia / Pedro M.G. Martins ; Managing the exchange-rate consequences of an MDG-related scale-up in HIV/AIDS financing / John Serieux -- pt. III. Public finance and debt relief. Gearing public finance to growth, employment and poverty reduction in Moldova / Terry McKinley ; Does debt relief increase fiscal space in Zambia? The MDG implications / John Weeks and Terry McKinley ; The reduction of fiscal space in Zambia - Dutch Disease and tight-money conditionalities / John Weeks -- pt. IV. Policies for transforming growth into employment generation. An employment-targeted economic programme for South Africa / Robert Pollin ... [et al.] ; A proposed strategy for growth, employment and poverty reduction in Uzbekistan / Terry McKinley and John Weeks ; Strengthening the employment impact of an MDG-based development strategy for Yemen / Terry McKinley.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: United Nations Development Programme; Manpower policy -- Developing countries; Poverty -- Government policy -- Developing countries; Developing countries -- Economic policy; Electronic books